1973
DOI: 10.1149/1.2403486
|View full text |Cite
|
Sign up to set email alerts
|

Generative and Stabilizing Processes in Tin-Palladium Sols and Palladium Sol Sensitizers

Abstract: An extensive study of sol systems produced by the reduction of solvated Pd by Sn2+ is presented. We show that the reaction is initiated by the formation of a polynuclear Sn‐Pd complex, which is autoreductive, yielding sol particles of a Sn‐Pd alloy core with a stabilizing layer of Sn2+ ions. The role of the Sn2+ stabilizing layer in controlling particle size is discussed in detail. We apply the knowledge of these systems to understand similar processes occurring in commercial Pd sol systems used for sensitizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 3 publications
4
79
0
Order By: Relevance
“…1. 19 The core of the each colloidal particle comprises of Pd-rich, zerovalent, crystalline Pd-Sn alloy, which functions as a catalytically active component for electroless deposition. The outer component of the shell consist of m-hydroxy-bridged Sn(II) and Sn(IV) oligomers which advocate the stabilization of catalytic particle against aggregation over the surface of polymer substrate by the virtue of inherent negative charge and hydrogen bonding interaction with water molecules and it also maintains the state of zerovalent Pd-Sn core required to catalyze the electroless deposition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. 19 The core of the each colloidal particle comprises of Pd-rich, zerovalent, crystalline Pd-Sn alloy, which functions as a catalytically active component for electroless deposition. The outer component of the shell consist of m-hydroxy-bridged Sn(II) and Sn(IV) oligomers which advocate the stabilization of catalytic particle against aggregation over the surface of polymer substrate by the virtue of inherent negative charge and hydrogen bonding interaction with water molecules and it also maintains the state of zerovalent Pd-Sn core required to catalyze the electroless deposition.…”
Section: Methodsmentioning
confidence: 99%
“…The outer component of the shell consist of m-hydroxy-bridged Sn(II) and Sn(IV) oligomers which advocate the stabilization of catalytic particle against aggregation over the surface of polymer substrate by the virtue of inherent negative charge and hydrogen bonding interaction with water molecules and it also maintains the state of zerovalent Pd-Sn core required to catalyze the electroless deposition. [19][20][21][22][23] Zabetakis et al reported that the adherence of b-stannic shells are critically important for the catalyzing the activity of the core for metal deposition but adhesion is generally weak and binding with the polymer surface occurs via van der Waals or other non-covalent interaction. 24 Therefore, surface activation was believed to be catalyzed by seeding of Pd(0) on the ber surface, resulting in development of nucleation site for the further deposition of metallic particles.…”
Section: Methodsmentioning
confidence: 99%
“…In the latter case [31][32][33], the oxidized substrate surface is directly activated by immersion in a colloidal solution obtained from an acidic mixture of tin chloride and palladium chloride. A further treatment (acceleration step) is still needed to allow the catalyst to be efficient.…”
Section: Electroless Depositionmentioning
confidence: 99%
“…Briefly, when the stamp is initially soaked in a sensitizing solution and subsequently washed in water, a gradient of [ . [30] Before the formation of the stabilizing layer, these complexes were free to aggregate and form larger particles whose radii, R, are characterized by an exponential distribution, F(R) = exp(±R/R av )/R av , where R av~1 .5 nm is the mean particle radius. [31,32] The Pd/Sn particles of various sizes diffused through the gel matrix.…”
Section: Film Roughnessmentioning
confidence: 99%